Length of Second-Stage Labor: Safety Considerations. Issue 6 (November 2016) - Simpson, Kathleen Rice
Abstract : Extending the duration of second stage labor beyond what has traditionally been considered standard may be beneficial in promoting vaginal birth. However, there are small but significant risks to mother and baby. Thus careful consideration, including periodic assessment of maternal and fetal wellbeing and chances of successful vaginal birth, should be occurring as a team. A collaborative discussion between the labor nurse and birth attendant that covers these two important clinical points at least every hour when second stage labor pushing exceeds 2 hours for nulliparous women and 1 hour for multiparous women may be a valuable safety measure.